Efficacy and Safety of Immunosuppressive Therapy for PBC–AIH Overlap Syndrome Accompanied by Decompensated Cirrhosis: A Real-World Study - Xiaoli Fan; Yongjun Zhu; Ruoting Men; Maoyao Wen; Yi Shen; Changli Lu; Li Yang (Canadian Journal of Gastroenterology and Hepatology)
Aim. To explore the efficacy and safety of immunosuppressive therapy for the treatment of primary biliary cirrhosis-autoimmune hepatitis (PBC-AIH) overlap syndrome accompanied by decompensated cirrhosis. Methods. A cohort study was performed to evaluate the usefulness of immunosuppressive therapy in this unique group. This cohort study was performed between October 2013 and June 2017 and included 28 biopsy-proven patients diagnosed according to the Paris criteria. The therapies included ursodeoxycholic acid (UDCA) alone (N=14) or in combination with immunosuppression (IS) therapy (N=14). The primary endpoints were biochemical remission, liver-related adverse events, transplant-free survival, and drug side-effects. Results. The frequency of biochemical remission for the AIH features was significantly higher in the UDCA+IS group than in the UDCA-only group (60.0 versus 9.1%, P=0.024) after 12 months of therapy but not after 3 and 6 months (28.6 versus 0%, P=0.165; 35.7 versus 7.1%, P=0.098). The rates of liver-related adverse events were lower in the combined group (2/14 versus 9/14, P=0.018). The Kaplan-Meier estimate showed that the transplant-free survival was distinct between the two groups (P=0.019). In the UDCA+IS group, mild and transient leukopenia occurred in two patients receiving azathioprine (AZA), and an infection was observed in one patient receiving mycophenolate mofetil (MMF). Conclusions. PBC-AIH patients with decompensated cirrhosis receiving a combination of UDCA and immunosuppressors presented with higher biochemical remission rates and experienced fewer liver-related adverse events, implying that the combined treatment might be a better therapeutic option for strictly defined decompensated PBC-AIH overlap syndrome.